2006
DOI: 10.1103/physrevb.74.224439
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial structure and half-metallic ferromagnetism inCo2MnSi-based magnetic tunnel junctions

Abstract: X-ray absorption ͑XAS͒ and x-ray magnetic circular dichroism ͑XMCD͒ techniques are utilized to explore the ferromagnetic/barrier interface in Co 2 MnSi full Heusler alloy magnetic tunnel junctions. Structural and magnetic properties of the interface region are studied as a function of the degree of site disorder in the alloy and for different degrees of barrier oxidation. Photoelectron scattering features that depend upon the degree of L2 1 ordering are observed in the XAS spectra. Additionally, the moments pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 30 publications
5
38
0
Order By: Relevance
“…This shoulder at the Co-L 3 peak is characteristic of full-Heusler alloys ͑Co 2 YZ͒ with the L2 1 structure and has been commonly observed for bulk samples 15 or thin films. 9,12 The XAS and XMCD spectra for the 4-ML-thick CMS film are similar to those for the 50-nm-thick film in terms of the structure and magnitude. The shoulder at the Co-L 3 peak ͑which is characteristic of Heusler alloys with the L2 1 structure͒ is also observed in the XAS spectrum for the 4-MLthick film, though it is not as clear as the shoulder for the 50-nm-thick film.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…This shoulder at the Co-L 3 peak is characteristic of full-Heusler alloys ͑Co 2 YZ͒ with the L2 1 structure and has been commonly observed for bulk samples 15 or thin films. 9,12 The XAS and XMCD spectra for the 4-ML-thick CMS film are similar to those for the 50-nm-thick film in terms of the structure and magnitude. The shoulder at the Co-L 3 peak ͑which is characteristic of Heusler alloys with the L2 1 structure͒ is also observed in the XAS spectrum for the 4-MLthick film, though it is not as clear as the shoulder for the 50-nm-thick film.…”
mentioning
confidence: 51%
“…2͑a͒-2͑d͒, there is a broad structure in the XAS and XMCD spectra at the higher photon energy ͑about 2 -10 eV͒ region of the Mn-L 3 XAS peak, which is also commonly observed for Co 2 MnZ. 9,12 The XAS and XMCD spectra in Figs. 2͑a͒-2͑d͒ indicate that no MnO existed in either film, because the formation of MnO in CMS films causes a characteristic multiplet structure in an XAS spectrum 19 and a serious reduction of the XMCD signals at the Mn edges, neither of which are observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such measurements were performed upon the series of samples for which dynamic measurements will be presented in the present paper and which have been labeled A x where x is the annealing temperature in the range of 300-500°C. 9 The Co and Mn x-ray absorption spectra revealed both x-ray absorption near edge structure ͑XANES͒ and extended x-ray absorption fine structure ͑EXAFS͒ oscillations that confirmed that L2 1 ordering improved with increasing annealing temperature. Magnetic moments were observed on both the Co and Mn sites, but for these samples the moment per 3d hole was found to be independent of annealing temperature in the range of 300-500°C at 0.35 B and 0.4 B for Co and Mn, respectively, 9 the number of 3d holes not being precisely known.…”
Section: Introductionmentioning
confidence: 64%
“…It has recently been shown that x-ray absorption spectroscopy ͑XAS͒ and x-ray magnetic circular dichroism ͑XMCD͒ measurements are powerful techniques for obtaining microscopic information about the element-specific electronic and magnetic states in the interfacial region of MTJs. [6][7][8][9] Our purpose of the present study is to clarify the electronic and magnetic states of the interfacial region of Co 2 YZ thin films facing a MgO barrier. For this study, we fabricated epitaxial CMS ultrathin films as typical Co 2 YZ films with an epitaxial MgO barrier and performed XAS and XMCD measurements at the Mn-L 2,3 and Co-L 2,3 edges.…”
mentioning
confidence: 99%